STRATEGI PENGEMBANGAN WISATA BUDAYA DI KELURAHAN RANDUACIR - Aletta Dewi Maria; Krisnawati Setyaningrum Nugraheni; Dyah Palupiningtyas (BADAN PENERBIT STIEPARI PRESS, 2022)
The city of Salatigaacts as a terminal (center) for trade in agricultural products for its private areas, a provider of tools and inputs for agricultural activities, as well as a center for the agricultural processing industry. This role is supported by the existence of the surrounding area which has great potential for agricultural development, both for food crops, fruit, vegetables, and other garden products. The success of this role will form a mutually beneficial relationship between Salatiga City and Semarang Regency